2013
DOI: 10.1158/1541-7786.mcr-12-0401
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Olaparib with Combination of Cisplatin on PTEN-Deficient Lung Cancer Cells

Abstract: PARP enzyme plays a key role in the cellular machinery responsible for DNA damage repair. PTEN is a tumorsuppressor gene deactivating PI3K downstream of EGFR signaling. We hypothesize that PTEN-deficient lung cancer cells suppressed DNA damage signaling and that the absence of PTEN can sensitize these cells to a concurrent treatment of a DNA-damaging agent (cisplatin) and a PARP inhibitor (olaparib). To investigate the effect of olaparib and cisplatin on PTEN-deficient lung tumors, two EGFR-mutant (deletion in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 41 publications
(54 reference statements)
2
40
0
Order By: Relevance
“…Co-treatment of PTENdeficient H1650 cells with cisplatin and the PARP inhibitor Olaparib, was more effective than each drug alone. When PTEN function was restored via transfection, this partially reduced this synergism [117]. The potential use of PARP inhibitors in the treatment of lung cancer was however questioned following results published from the ECLIPSE trial of 780 NSCLC patients, which combined the PARP inhibitor Iniparib with a carboplatin and gemcitabine regimen, an approach that had previously proven to be of benefit in triple-negative breast cancer patients [110].…”
Section: Poly (Adp-ribose) Polymerasesmentioning
confidence: 99%
“…Co-treatment of PTENdeficient H1650 cells with cisplatin and the PARP inhibitor Olaparib, was more effective than each drug alone. When PTEN function was restored via transfection, this partially reduced this synergism [117]. The potential use of PARP inhibitors in the treatment of lung cancer was however questioned following results published from the ECLIPSE trial of 780 NSCLC patients, which combined the PARP inhibitor Iniparib with a carboplatin and gemcitabine regimen, an approach that had previously proven to be of benefit in triple-negative breast cancer patients [110].…”
Section: Poly (Adp-ribose) Polymerasesmentioning
confidence: 99%
“…The results showed that catalytic PARP inhibitors are highly effective in combination with camptothecins, whereas PARP inhibitors capable of PARP trapping are more effective with temozolomide and provided insights in combination treatment rationales for different PARP inhibitors. A synergistic effect of olaparib with a combination of cisplatin was observed in PTEN-deficient lung cancer cells wherein the mechanistic investigations revealed that PTEN deficiency caused reductions in nuclear RAD51 and RPA focus formation and phosphorylated Chk1 and Mre11, which also indicated that genetic inactivation of PTEN might lead to the suppression of DNA repair in the tumor cells [110]. Efficacy of Carboplatin Alone and in Combination with ABT888 in intracranial murine models of BRCA-Mutated and BRCA-wild-type TNBC has been reported [76].…”
Section: Parp Inhibitors As Chemo/radiopotentiating Agents: Tnbc and mentioning
confidence: 97%
“…Aside from killing BRCA-mutant cancers, PARP inhibitors have also been shown to be synthetically lethal with a variety of other HR dysfunctions, thus extending the potential patient population that may benefit from these agents. 23,[153][154][155][156][157][158][159][160][161][162][163] This phenomenon, named "BRCAness", includes deficiency in the DDR players such as ATM, in T-cell pro-lymphocytic leukemia, B-cell chronic lymphocytic leukemia, mantle cell lymphoma and breast cancer; 156,157,159,164,165 checkpoint kinase 2 (CHEK2, best known as CHK2), in sarcoma, breast cancer, ovarian cancer and brain tumors; 166 phosphatase and tensin homolog (PTEN), in glioblastoma as well as prostate, lung and endometrial cancers; [167][168][169][170][171] and meiotic recombination 11 homolog A (MRE11A), in colorectal cancer and myeloid malignancies. [172][173][174] Of relevance in the context of cancer therapy, basal-like triple negative breast cancers (TNBC), an aggressive subtype of breast cancer frequently associated with poor prognosis, 175 are believed to have BRCAness phenotype and may thus be targeted by PARP inhibitors.…”
Section: Parp1 In Cancer Therapymentioning
confidence: 99%